Carinal sleeve resection: last exit for bronchial insufficiency—a 17-year, single-centre experience. (27th March 2021) - Herrmann, Dominik; Oggiano, Melanie; Gencheva-Bozhkova, Plamena; Braun, Monique; Neuhaus, Gerd; Ewig, Santiago; Hecker, Erich
Abstract: : OBJECTIVES: Bronchopleural fistula after pneumonectomy and dehiscence of an anastomosis after sleeve lobectomy are severe complications. Several established therapeutic options are available. Conservative treatment is recommended for a small fistula without pleural infection. In patients with a bronchopleural fistula and subsequent pleural empyema, surgical management is the mainstay. Overall, the associated morbidity and mortality are high. Carinal sleeve resection is the last resort for patients with a short stump after pneumonectomy or anastomotic dehiscence after sleeve resection near the carina. METHODS: All patients with bronchopleural fistula after pneumonectomy or sleeve resection who underwent secondary carinal sleeve resection between 2003 and 2019 in our institution were evaluated retrospectively. Patients with anastomotic dehiscence after sleeve lobectomy underwent a completion pneumonectomy. The surgical approach was an anterolateral thoracotomy; the anastomosis was covered with muscle flap, pericardial fat or omentum majus. In case of empyema, povidone-iodine-soaked towels were introduced into the cavity and changed at least twice. RESULTS: A total of 17 patients with an initial sleeve lobectomy in 12 patients and pneumonectomy in 5 patients were treated with carinal sleeve resection in our department. Morbidity was 64.7% and 30-day survival was 82.4% ( n = 14). A total of 70.6% of the patients survived 90 days ( n = 12). Median hospitalization was 17 days and the median stay in the intensive care unit was 12 days. CONCLUSIONS: Carinal sleeve resection is a feasible option in patients with a post-pneumonectomy fistula or anastomotic insufficiency following sleeve lobectomy in the absence of alternative therapeutic strategies. Nevertheless, postoperative morbidity is high, including prolonged intensive care unit stay.